Measuring Fathers' Responses to Negative Emotions in Children: SF-CCNES Adaptation in Indonesia - Bahrain, Sabila; Royanto, Lucia RM (Syntax Literate, 2025)
Fathers’ roles in emotion socialization remain understudied in Indonesia, where patriarchal norms often limit their involvement (Komisi Perlindungan Anak Indonesia, 2021). Existing tools like the CCNES are lengthy, prompting the need for a concise alternative. This study adapts and validates the Indonesian SF-CCNES (King et al., 2023) to measure fathers’ responses to children’s negative emotions. Following Beaton et al. (2000)’s cross-cultural adaptation guidelines, the SF-CCNES was translated, back-translated, and reviewed by experts. Data from 292 fathers of children aged 3–6 were analyzed using Confirmatory Factor Analysis (CFA) and reliability tests. The 17-item Indonesian SF-CCNES demonstrated strong reliability (α = 0.733–0.845) and validity (factor loadings >0.3), though item 1A required revision due to cultural misinterpretation. This validated tool aids research on paternal emotion socialization in Indonesia and informs interventions to enhance fathers’ emotional responsiveness.